Para além do consumo conspícuo : uma proposta de interpretação da teoria do consumo em Thorstein Veblen - Camatta, Rafael Barbieri (2014)
The consumption issues are central to the economic theory, and were approached by various microeconomic schools and as well by other disciplines as Administration, Marketing, Psychology, Sociology, etc. This Dissertation tries to demonstrate the importance of Thorstein Veblen contribution to the theme, primarily by the inclusion of instincts, habits and institutions in the analysis. To this purpose, the study initiate with a historical retrospective of the decades that Veblen wrote his most important works. As the historical phenomena are discussed, there are indications of how those have influenced Veblen’s works. Afterwards, the Veblen’s decision making process is presented, with specific sections to instincts and habits/institution, as well as the interrelation between those factors. This analysis initiate with an overview of the marginalist theory of consumption (the marginal utility theory), and Veblen’s critic to this point of view. Those sections are important to express the origin point of Veblen epistemological proposition for an evolutionary economics. Subsequently, the decision making process is analyzed per se. Over this process lies all Veblen’s consumption theory, both the conspicuous and the standardized. Finally, the primary objective of this Dissertation is investigated, first by the survey of Veblen’s Conspicuous Consumption Theory, the original proposition, than its latter unfolding research, the marginal interpretation. In these section the research attempt to expose in which points the marginal interpretation of the Conspicuous Consumption advances as well in which points it deviates from the original proposition. Finally, from the analysis of The Theory of Business Enterprise book, the research indicates that Veblen’s consumer theory is not restricted to the Conspicuous Consumption of luxury brands. Otherwise, with the introduction of standardized consumption concept, this theory embodies the wage goods as well.